Preparation of cubic ordered mesoporous silicon carbide monoliths by pressure assisted preceramic polymer nanocasting - Wang, Jiacheng; Oschatz, Martin; Biemelt, Tim; Lohe, Martin R.; Borchardt, Lars; Kaskel, Stefan (Microporous and Mesoporous Materials, 2013)
Ordered mesoporous silicon carbide monoliths (OMSCMs) with three-dimensional (3D) bi-continuous cubic structure (Ia3d) have been successfully prepared using KIT-6 silica as the hard template and the commercial polycarbosilane (PCS-800) as the preceramic precursor. Tablet-like SiC/KIT-6 composite monoliths were formed via nanocasting of PCS-800 into the mesopores of KIT-6 silica by the wet impregnation, followed by pressing the PCS-800/KIT-6 composite powder with the addition of triblock copolymer P123 as a binder, and subsequent pyrolysis at 1073, 1273, or 1473 K in argon. The KIT-6 silica template was then dissolved in hydrogen fluoride (HF) solution to generate the silicon carbide (SiC) replicated monoliths with cubic ordered mesoporous structure. The OMSCMs demonstrated good macroscopic tablet-like appearances and no any cracks could be found in spite of the evident shrinkage. They were characterized by small-angle and wide-angle X-ray diffraction (XRD), nitrogen adsorption, Fourier-transform infrared (FT-IR), elemental analysis, transmission electron microscopy (TEM), and scanning electron microscopy (SEM). Nitrogen adsorption and small-angle XRD measurements showed that the OMSCMs had very high stability even after re-treatment at 1673 K under argon. And the transformation of amorphous into nano-crystalline state for SiC framework in the OMSCMs proceeded with the retention of the tablet-like morphology. © 2012 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: KIT-6 silica; Mesoporous materials; Monolith; Nanocasting; Silicon carbide